Effect of typhoon with extreme precipitation on mountain reservoir drinking water treatment: a case study in Ningbo, China. Issue 2 (3rd April 2017) - Chen, Wei; Zhou, Zhengxie; He, Jianrong; Tao, Hui; Liu, Zhigang
ABSTRACT: Due to frequent drinking water pollution accidents in the past decade, it is common that mountain reservoirs were used as the source of drinking water in China. However, some coastal areas frequently suffer from typhoon with extreme precipitation, which results in the water quality deterioration of the reservoirs. The influence of typhoons with extreme precipitation on Jiaokou reservoir and the emergency treatment process of Maojiaping water treatment plant in the past three typical typhoons with extreme precipitation from the year of 2012–2015 were studied. It was found that the degradation of water quality, such as the increase of turbidity and bacteria index, may not merely appear during the events, but last for several days. Changing the dosage of water purification agent, such as coagulant and disinfectant at right time and place may be an efficient emergency water treatment process. Based on the analysis of water quality variation rule during and after the events, it was also found that emergency treatment can be fully prepared before the arrival of a typhoon with extreme precipitation. And in order to better respond to the typhoon with extreme precipitation, several suggestions are also proposed in this paper as follows: establishing vegetated buffers at right place, such as macrophanerophytes, shrub or herbage, increasing investments in infrastructure management, merging or cancelling the small-scale water treatment plants, preparing adequate water purification agent before the typhoon comes, etc.